2015
DOI: 10.1128/jcm.03069-14
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Sphingomonas koreensis as a Human Pathogen in a Patient with Meningitis

Abstract: c Sphingomonas koreensis is an aerobic Gram-negative rod originally described in 2001 following isolation from natural mineral water in Korea. Here, we report a case study with Sphingomonas koreensis as the causative agent of meningitis. To our knowledge, this is the first documented case of Sphingomonas koreensis as a human pathogen. CASE REPORT In 1997, a 14-year-old female patient underwent surgery due to a syrinx in the cervical portion of her medulla. A cystoperitoneal shunt system was inserted, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Since these reports are based on nonsequencing methods (e.g., pulsed-field gel electrophoresis and blood cultures), it was not possible to perform a more detailed comparison to the isolates and populations recovered in the present study. 16S rRNA gene sequence analysis showed that the closest relative for several of our isolates was Sphingomonas koreensis (99% nucleotide identity), which has been identified as the causative agent of meningitis in at least one previous study (70). Taken together, it is likely that the Sphingomonas isolates recovered here represent opportunistic pathogens.…”
Section: Resultsmentioning
confidence: 68%
“…Since these reports are based on nonsequencing methods (e.g., pulsed-field gel electrophoresis and blood cultures), it was not possible to perform a more detailed comparison to the isolates and populations recovered in the present study. 16S rRNA gene sequence analysis showed that the closest relative for several of our isolates was Sphingomonas koreensis (99% nucleotide identity), which has been identified as the causative agent of meningitis in at least one previous study (70). Taken together, it is likely that the Sphingomonas isolates recovered here represent opportunistic pathogens.…”
Section: Resultsmentioning
confidence: 68%
“…Sphingomonas koreensis represents a human pathogen (Marbjerg et al . ), but information about the pathogenicity of other species of this genus is still lacking. Salmonella enterica , a food‐borne pathogen associated with pork products, was isolated from one enlarged ICLN.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterium-specific PCR has not been widely used in the diagnosis of meningitis in newborn babies since it can be caused by many types of bacteria: some more common (e.g. Group B Streptococcus, Escherichia coli) [12][13][14]35], some less so [23][24][25][26][27][28][29][30][31][32][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%